1999
DOI: 10.1901/jaba.1999.32-25
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Stimulus Overselectivity With Nonverbal Differential Observing Responses

Abstract: Three individuals with mental retardation exhibited stimulus overselectivity in a delayed matching-to-sample task in which two sample stimuli were displayed on each trial. Intermediate accuracy scores indicated that participants could match one of the samples but not both of them. Accuracy in a baseline condition was compared to accuracy with a differential observing response procedure. This procedure prompted participants to make simultaneous identity-matching responses that required observation and discrimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
167
3
16

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(196 citation statements)
references
References 16 publications
10
167
3
16
Order By: Relevance
“…Instances of overselective responding are found in many populations that experience some assault to their levels of cognitive function, including individuals with intellectual disabilities (Smeets et al 1985), learning disabilities (Bailey 1981;Dube and McIlvane 1999), Rett's Disorder (Fabio et al 2009), acquired brain injury (Wayland and Taplin 1982), schizophrenia (Feeney 1972), and Autism Spectrum Disorders (ASD; Kelly et al 2015;Leader et al 2009;Reed et al 2009;Frankel et al 1984). Moreover, previous research investigating overselectivity in typically developing adults has demonstrated that adding a cognitive load can induce higher levels of over-selective responding (Reed and GibsonAs might be predicted by the increasing problems with cognitive capacity and attention deficits that can be noted with age (Chao and Knight 1997), higher levels of over-selectivity have also been noted in older people (Gard et al 2014;McHugh et al 2010;McHugh and Reed 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Instances of overselective responding are found in many populations that experience some assault to their levels of cognitive function, including individuals with intellectual disabilities (Smeets et al 1985), learning disabilities (Bailey 1981;Dube and McIlvane 1999), Rett's Disorder (Fabio et al 2009), acquired brain injury (Wayland and Taplin 1982), schizophrenia (Feeney 1972), and Autism Spectrum Disorders (ASD; Kelly et al 2015;Leader et al 2009;Reed et al 2009;Frankel et al 1984). Moreover, previous research investigating overselectivity in typically developing adults has demonstrated that adding a cognitive load can induce higher levels of over-selective responding (Reed and GibsonAs might be predicted by the increasing problems with cognitive capacity and attention deficits that can be noted with age (Chao and Knight 1997), higher levels of over-selectivity have also been noted in older people (Gard et al 2014;McHugh et al 2010;McHugh and Reed 2007).…”
mentioning
confidence: 99%
“…This theory posits that over-selective responding is caused by an inability to attend to all component elements of a stimulus. Stimuli that are not attended to cannot be processed or learned about; therefore, only the elements of the stimulus that are attended to can subsequently control behavior (e.g., Dube and McIlvane 1999;Koegel and Wilhelm 1973;Lovaas et al 1971). An alternative view is suggested by the comparator theory of stimulus over-selectivity, which suggests that a comparator mechanism is responsible for selecting between stimuli that potentially could be responded to, and triggers responses only to the most important stimuli available (see Reed 2011).…”
mentioning
confidence: 99%
“…Ou seja, ao invés de responder ao estímulo como um todo (sentença completa), o participante estava sob controle de algum componente da sentença. Provavelmente, a introdução de procedimentos de respostas de observação diferencial (Dube & McIlvane, 1999) poderia fortalecer o controle discriminativo do responder.…”
Section: Resultsunclassified
“…O controle restrito de estímulos tem sido amplamente documentado em pessoas com necessidades educacionais especiais (Bickel & cols., 1984;Bickel & cols., 1986;Lovaas & cols., 1979;Meisel, 1981;Wilhelm & Lovaas, 1976), limitando a aquisição de novos comportamentos. Esse controle pode ser reduzido por procedimentos de ensino que estabelece a resposta diferencial de observação (Dube & McIlvane, 1999). O controle restrito ou parcial tem sido apontado como um dos fatores principais responsáveis pelas dificuldades em leitura.…”
Section: K R S Alves E Colsunclassified
“…Para a análise do controle parcial, foram aplicadas sondas de controle silábico adaptadas do estudo de Stromer, McIlvane, Dube e Mackay (1993) Dube & McIlvane, 1999;Stromer & cols., 1993), a direção a ser tomada é a de estender a análise da superseletividade de estímulos para a análise do controle parcial pelas sílabas no ensino de leitura generalizada em pessoas com necessidades educacionais especiais.…”
Section: K R S Alves E Colsunclassified